Photovoltaic water pumping system for small power conventional AC pumps - Tangerino, Bruno Henrique Boschetti (2020)
The interest of photovoltaic (PV) water pumping systems with standard components is increasing as a low cost and independent solution over dedicated systems. However, one of the challenges of this alternative is the fact that small power systems to drive power pumps require a small number of PV modules and the PV string voltage is, usually, not enough to feed the frequency converter. This paper presents an approach to the drive, using a DC/DC converter with maximum power point tracking (MPPT). The overall system has been tested on a real experimental platform.